PERAN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR MADRASAH IBTIDAIYAH - Arif Prasetyo; Roihan Sadad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Facilities and infrastructure play an important role in supporting the sustainability of educational institutions. The school is responsible for its management, including planning and maintenance. With adequate facilities, the teaching and learning process can take place effectively and efficiently. The research method used is qualitative research with a literature study approach, where the sources used are books and journals that are in accordance with the material being discussed. However, in reality, sometimes the standardization of school facilities and infrastructure is still lacking, causing a problem. The conclusion of this study is that well-maintained facilities and infrastructure in elementary schools and Islamic elementary schools can support effective learning, save repair costs, and shape student character. Good maintenance can create a comfortable learning environment and improve the image of the school